Matrix reloaded (Philippines : Warner Bros, 2003)
Sentinels swarm. Smith clones. Neo flies...but perhaps not even a chosen one gifted with astonishing new powers can stop the advance of the Machines. Neo. Morpheus. Trinity. They're back for the powerful second chapter of the Matrix trilogy, and exciting new allies join them in the struggle against foes who are cloned, upgraded and closing in on humanity's last enclave. Back, too, are the Wachowski Brothers and producer Joel Silver, expanding their vision with a spectacle that rocks the senses, proves the heart and shapes filmmaking's tomorrows. What is The Matrix? The question is not yet fully answered. And it leads to another: Who created the Matrix? The answers lead to more worlds of bold possibility - and to a destiny that passes from revelations to Revolutions.